Enzymatic Hydrolysis And Yeast Fermentation Of Okara - Ramli, Saadiah (Pusat Pengajian Teknologi Industri, 2020)
The production of soybean-based product results in an insoluble residue called okara. This byproduct that rich in protein, fat, and fiber nowadays was discarded as an agro-waste due to its poor properties such as easily putrefy and has high content of insoluble dietary fiber. To overcome this problem, a valorization of okara by the biological treatment could become one of the promising approaches to improve the nutritional value of okara. The objectives of this study were to determine optimum enzymatic hydrolysis condition on the release of total sugar by Viscozyme L and investigate the total protein content of okara after fermentation by Saccharomyces cerevisiae. The optimization of the enzymatic hydrolysis was carried out using response surface methodology (RSM) by R software. The effect and interaction of three variables; concentration of enzyme (1-5% v/w), temperature (25-50°C) and pH (3.5-5.5) were investigated to obtain the maximum release of total sugar. The results of ANOVA analysis showed a significant effect of these three variables on the release of total sugar content. The highest total sugar content of 1000 ug/mL was obtained on optimal condition of enzymatic hydrolysis at 24°C, enzyme concentration of 4.8% (v/w) and pH 5.5. Fermentation of okara with S. cerevisiae found a change in yeast viability over 72 hours. Yeast cell utilized total sugar as the main sources to undergo aerobic fermentation. The fermentation-treated okara slurry contained a composition of neutral sugars including sucrose, glucose, and fructose. The total protein content was increased from 19.43% to 26.88% on a dry basis. Therefore, okara treated with enzyme and S. cerevisiae could improve the value and properties of okara afterwards